Una società senza genere? Il potere trasformativo dell’utopia - Anna Carreri; Barbara Poggio (Cambio)
This contribution is aimed at shedding light on how the concept of utopia is closely linked, both in terms of content and method, to the gender perspective and, more specifically, to feminist reflection. We do so by dwelling on some of the most influential voices that have contributed to the recent rediscovery of utopia as a sociological method and mobilizing force for critiquing and reacting to advanced capitalism and existing arrangements of gender relations.The article closes with some reflections on how utopian realism can enable us to overcome the fear of change in gender relations and counter the risk of “retrotopias”.